Effect of Bhavana on Qualitative Phytochemical Profile and Elemental Composition of Shilajathu: A Comparative Pharmaceutical Study With Ekanayaka Kwatha Bhavitha Shilajathu - Anjala P S; Rajam R (International Journal of Ayurveda and Pharma Research, 2025)
Shilajathu, a revered Ayurvedic Rasayana, is subjected to Bhavana, a traditional processing technique. This study investigates the effect of Bhavana on Shilajathu's phytochemical profile and elemental composition using Ekanayak Kwatha Bhavitha Shilajathu. Ekanayaka (Salacia chinensis) is a prominently featured drug in various Kashayas recommended for Prameha Chikitsa in esteemed Kerala texts, such as Sahasrayoga and Chikitsamanjari. Ekanayaka Kwatha Bhavitha Shilajathu was prepared through a seven-fold Bhavana process. Phytochemical screening revealed a diverse profile of bioactive compounds. HPTLC analysis confirmed the presence of Mangiferin, a standard biomarker for Ekanayaka in Ekanayak Kwatha Bhavitha Shilajathu, and also revealed enhanced bioactive compounds in Bhavitha Shilajathu compared to Shilajathu before Bhavana. Energy Dispersive X-ray Analysis showed increased weight % of certain elements, C, Na, Mg, Cl, and K in Bhavitha Shilajathu. The findings demonstrate enhanced absorption of Ekanayaka Kwatha's active principles into Shilajathu during Bhavana. The formulation's safety was confirmed by detecting heavy metal levels within permissible limits. The study provides insights into the Ayurvedic concept of Bhavana and its effects on Shilajathu's phytochemical and elemental composition.